Answer:
(8,5)
Step-by-step explanation:
x=8
5*8-2y=30
40-2y=30 . subtract 40 from both sides
-2y=-10 . divide both sides by-2
y=5
15%=3
5%=1
5(20)=100
1(20)=20
So, there are 20 students in the class.
Step 1: Make sure that the trinomial is written in the correct order; the trinomial must be written in descending order from highest power to lowest power.
Step 2 : Decide if the three terms have anything in common, called the greatest common factor or GCF. If so, factor out the GCF. Do not forget to include the GCF as part of your final answer.
Step 3 : Multiply the leading coefficient and the constant, that is multiply the first and last numbers together.
Step 4 : List all of the factors from Step 3 and decide which combination of numbers will combine to get the number next to x.
Step 5 : After choosing the correct pair of numbers, you must give each number a sign so that when they are combined they will equal the number next to x and also multiply to equal the number found in Step 3.
Step 6 : Rewrite the original problem with four terms by splitting the middle term into the two numbers chosen in step 5.
Step 7 : Now that the problem is written with four terms, you can factor by grouping.
you cant add or subtract or multiply or divide if the variables arent the same so the simplified version of <span>-3x²ym + 7x - 5ymx² + 16x would be
</span> -3x²ym <span>- 5ymx² + 23x</span>
Answer:
The solution to the system of equations is:
x = 2, and y = -1
Explanation:
Given the pair of equations:
4x + 5y = 3 ..........................................................................(1)
2x + 3y = 1............................................................................(2)
To solve this by elimination:
Multiply equation (2) by 2, to eliminate x
Equation (2) becomes
4x + 6y = 2 .........................................................................(3)
Subtract equation (1) from (3)
4x - 4x + 6y - 5y = 2 - 3
y = -1 ....................................................................................(4)
Multiply equation (1) by 3 and equation (2) by 5 to eliminate y
Equation (1) becomes
12x + 15y = 9 .......................................................................(5)
Equation (2) becomes
10x + 15y = 5 ........................................................................(6)
Subtract equation (6) from (5)
12x - 10x + 15y - 15y = 9 - 5
2x = 4
Divide both sides by 2
x = 4/2 = 2 ............................................................................(7)
From equations (7) and (4)
x = 2, and y = -1